Designing, assembly and start up for a semiautomatic hot-air tray dryer (2010)
Designing specific equipment as a teaching and investigation tool in engineering is an interesting alternative for reducing costs and contributing towards local appropriation of know- ledge and technology. It makes adaptation to the environment easier and reduces technology dependency. This work shows how a semiautomatic hot-air tray-dryer was designed, built and brought into operation, describing the pertinent engineering stages. The dryer was controlled by using Microsoft Visual Basic and could simulate environmental conditions (temperature and humidity) anywhere in Colombia. Drying curves for Dominico Hartón variety banana were made for two temperatures (50°C and 70°C), in duplicate, to validate the equipment.